Observations on the Relationof Vegetation to mass-wasting Processes in the Mesters Vig District, Northeast Greenland. - Raup, Hugh M. (Meddelelser om Grønland, 1969)
This paper is a botanical companion piece to Dr. A. L. WASHBURN'S publication on his instrumental observations of mass-wasting. It contains botanical analyses of the experimental sites reported in that publication: nos. 6, 7 and 8, 15, 16, and 17. For each experimental site there are descriptions of topography and soils, the moisture supply, frost heaving, downslope movement of targets by gelifluction and frost creep, and disturbance by erosion or other processes found to be active in the sites. The flora and distribution of vegetation types are described for each site, and the differing types of vegetation are analyzed in terms of the occurrence and behavior of their species on gradients of ground coverage, moisture, and physical disturbance of the soil. The study is summarized in terms of habitats rather than experimental sites, using analysis by species tolerance ratings on the gradients mentioned above. The paper contains suggestions for at least a partial rationalization of the open vegetation of the fjaeld-mark, proposing that external limiting factors should be assessed in light of the inherent capacities of the species to survive or utilize variations in the factor gradients. Second, the study is at least a partial test of the methods of analysis used, to see whether the basic information gathered from observations on species' tolerance in the whole Mesters Vig district could be applied to specific sites at large map scales.